The truth about man and for man. Practical implications of John Paul II’s encyclical “Fides et ratio” - Ryszard Hajduk (Polonia Sacra, 2024)
Twenty-five years ago, John Paul II’s encyclical Fides et ratio was published, where the question of truth occupies a central place. The task of the Church is to transmit to people the truth revealed by Jesus Christ, which discloses the mystery of God and man, is accessible in faith, and appeals to the intellect to accept it. In these times, dominated by a pragmatic approach to reality, a question arises about the practical, existential meaning of the truth proclaimed by the Church. The content analysis of the papal teaching in “Fides et ratio” leads to the conclusion that the truth cannot be reduced to a set of ideas that enrich human cognition. Therefore, the ecclesial ‘diakonia’ of truth serves human life because it helps man use his freedom properly and leads him to the fullness of humanity. The truth allows man to protect himself from relativism and religious egalitarianism threats. The communication of truth should consider people’s needs to perceive it as a precious gift from God, not as a yoke.